Validation of a Model-based Method for Estimating Functional Volume Gains during Recruitment Manoeuvres in Mechanical Ventilation. Issue 27 (2018) - Morton, Sophie E.; Knopp, Jennifer L.; Docherty, Paul D.; Shaw, Geoffrey M.; Chase, J. Geoffrey
Abstract: Mechanical ventilation is a core therapy for patients suffering from respiratory failure in an intensive care unit. However, incorrect ventilator settings can cause further lung damage due to the heterogeneity of lung diseases. A common lung protective strategy is titrating Positive end-expiratory pressure (PEEP) to minimum elastance during a staircase recruitment manoeuvre. Increases in applied PEEP can result in additional lung volume due to alveolar recruitment. However, excessive increases in pressure risks ventilator induced lung injury (VILI). Thus, a trade-off must be made between maximising recruitment and minimising risk. In this study, a non-invasive and clinically relevant model-based method to predict the quantity of this additional volume is developed and the accuracy assessed against measured volume changes. Initial results show reasonable accuracy in estimating gained volume with median [IQR] error of 40 [20 – 60] mL in PEEP changes of up to 9 cmH2 O. Use of this parameter to predict lung mechanics at a higher PEEP level was also assessed and had an absolute median [IQR] error of 1.0 [0.5 – 1.8] cmH2 O in predicting peak inspiratory pressure. These results offer an opportunity for clinicians to better optimise PEEP selection as patient condition evolves.